Stretcher Adapted to Transportation of a Patient in Marine Conditions – a Design Proposal - Jursza, P. (Scientific Journal of Gdynia Maritime University, 2018)
The article presents design of stretcher adapted to transport harmed in marine conditions, construction of which allows functioning in conditions of: high waves, strong winds and highly aggressive impact of the marine environment on individual elements of the stretcher. The role of the design is to help increase safety of injured at sea.